Public providers, versus private providers, of public goods: A general equilibrium study of the role of the state - George Economides; Apostolis Philippopoulos; Vanghelis Vassilatos (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper studies the difference between public production and public finance of public goods in a dynamic general equilibrium setup. By public finance, we mean that the public good is produced by private providers with the government financing their costs. When the model is calibrated to match fiscal data from the UK economy, the main result is that, ceteris paribus, a switch from public production to public finance can have substantial aggregate and distributional implications. Public providers cannot beat private providers in terms of aggregate efficiency. We finally design a transfer scheme that can make a switch to private provision welfare improving for all agents including public employees.
Keywords: H40; D90; D60; 330; public goods; growth; welfare; Öffentliches Gut; Privatwirtschaft; Öffentliche Ausgaben; Wirtschaftliche Effizienz; Wirtschaftswachstum; Wohlfahrtseffekt; Theorie